Fate of dynamical phase transitions at finite temperatures and in open systems - Sedlmayr, Nicholas; Fleischhauer, Michael; Sirker, J. (Physical Review B, 2018)
When a quantum system is quenched from its ground state, the time evolution can lead to nonanalytic behavior in the return rate at critical times tc. Such dynamical phase transitions (DPTs) can occur, in particular, for quenches between phases with different topological properties in Gaussian models. In this paper we discuss Loschmidt echos generalized to density matrices and obtain results for quenches in closed Gaussian models at finite temperatures as well as for open-system dynamics described by a Lindblad master equation. While cusps in the return rate are always smoothed out by finite temperatures we show that dissipative dynamics can be fine-tuned such that DPTs persist.
CRIS-Team Scopus Importer:2023-03-27